UX on the go : a flexible guide to user experience design - Mara, Andrew (Associate Professor) (New York, NY : Routledge, 2020)
"Designed with flexibility and readers' needs in mind, this purpose driven book offers new UX practitioners succinct and complete intructions on how to conduct user research and rapidly design interfaces and products in the classroom or the office. With sixteen challenges to learn from, this comprehensive guide outlines the process of a User Experience project cycle from assembling a team to researching user needs to creating and veryifying a prototype. Practice developing a prototype in as little as a week or build your skills in two, four, eight, or sixteen week stretches. Gain insight into individual motivations, connections, and interactions; learn the three guiding principles of the design system; and discover how to shape a user's experience to achieve goals and improve overall immediate experience, satisfaction, and well-being. Written for professionals looking to learn or expand their skills in user experience design and students studying technical communication, information technology, web and product design, business, or engingeering alike, this accessible book provides a foundational knowledge of this diverse and evolving field. A companion website will include examples of contemporary UX projects, material to illustrate key techniques, and other resources for students and instructors. Access the material at uxonthego.com"--
OCLC-licensed vendor bibliographic record.
Keywords: Consumer satisfaction; User interfaces (Computer systems) -- Design; LANGUAGE ARTS & DISCIPLINES / Communication